Analysis of the Behavior of Registration Officers in Preventing Covid-19 at Mandau Hospital in 2022: Analisis Perilaku Petugas Pendaftaran Dalam Pencegahan Covid-19 Di RSUD Mandau Pada Tahun 2022 - Brenda Yeni; Arief Wahyudi; Welly Sando (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
The registration section is the most important and important part for the hospital. In this section, the risk of disease transmission is very large, because the registration officer makes direct contact with the patient or the patient's family. Therefore, various efforts need to be made to reduce the high transmission of diseases including the COVID-19 virus. The purpose of this study was to analyze the behavior of registration officers in preventing COVID-19 at the Mandau Hospital in 2022. This study used an analytical research methodology with a qualitative approach carried out at the Mandau Hospital from February to March 2022. The main informants consisted of 3 registration officers, informants The key is the head of the medical record installation and the patient. The supporting informant is the head of HR. Data collection techniques using interviews and observation. Data processing using data triangulation method. The results showed that there were still policy violations where officers did not always wear masks, could not always keep their distance and did not wash their hands regularly. The attitude towards preventing COVID-19 is good, the existing infrastructure is complete, but the supervision of health protocols is still not optimal. Suggestions for the Mandau General Hospital to carry out supervision and application of sanctions, to collaborate across sectors in preventing COVID-19 cases by involving cross-sectors.